THE ROLE OF BIG DATA IN IMPROVING TAX COMPLIANCE - Loso Judijanto; Al-Amin (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The use of Big Data has brought many benefits in various sectors, one of which is in improving tax compliance. This abstract discusses the role of Big Data in improving the taxation system through more in-depth and accurate data analysis of taxpayer behaviour. By utilising Big Data technology, tax authorities can identify potential non-compliance and optimise the audit process, as well as personalise services and communications to taxpayers. In addition, Big Data contributes to increased transparency and accountability in taxation, which ultimately encourages higher tax compliance and creates a more efficient and fairer taxation system.